The Factors Causing Changes in Adolescent Nutritional Status During The Covid-19 Pandemic - Ajeng Tresna Maihan Dawami; Linda Riski Sefrina (Poltekkes Kemenkes Mataram, 2022)
Background. The COVID-19 pandemic has caused many changes, one of which is the nutritional status of adolescents. There is an increase and decrease in nutritional status, which significantly affects the health status of individuals. According to Basic Health Research data (2018), the prevalence of being very underweight in adolescents aged 13-15 is 1.9%, and obesity in adolescents aged 13-15 is 4.8%. Meanwhile, the prevalence of very thin and obese in adolescents aged 16-18 years was 1.4% and 4%, respectively.Research Methods. This research is a literature review reviewing several studies as sources of information. The research used in this research is the last five years' research which sinta accredits.Research Result. This study shows the results of changes in nutritional status either increase or decrease. This is caused by several factors, namely the role of parents, physical activity, peers, social media, exercise habits, and consumption patterns. One of the main factors that cause changes in nutritional status is changes in activity in adolescents due to social movements. Conclusion. The COVID-19 pandemic has caused many changes in various sectors, including education. One of those who have recovered from the COVID-19 pandemic is teenagers. Most adolescents experience changes in nutritional status during the pandemic. This is because most teenagers learn with courage, resulting in reduced activity. In addition, several other factors also influence changes in adolescent nutritional status, such as the role of parents, social media, peers, exercise habits, and consumption patterns.